Multicenter study on the diagnostic performance of multiframe volumetric laser endomicroscopy targets for Barrett's esophagus neoplasia with histopathology correlation. Issue 12 (1st July 2020) - Struyvenberg, M R; de Groof, A J; Kahn, A; Weusten, B L A M; Fleischer, D E; Ganguly, E K; Konda, V J A; Lightdale, C J; Pleskow, D K; Sethi, A; Smith, M S; Trindade, A J; et al.
Abstract: Volumetric laser endomicroscopy (VLE) has been shown to improve detection of early neoplasia in Barrett's esophagus (BE). However, diagnostic performance using histopathology-correlated VLE regions of interest (ROIs) has not been adequately studied. We evaluated the diagnostic accuracy of VLE assessors for identification of early BE neoplasia in histopathology-correlated VLE ROIs. In total, 191 ROIs (120 nondysplastic and 71 neoplastic) from 50 BE patients were evaluated in a random order using a web-based module. All ROIs contained histopathology correlations enabled by VLE laser marking. Assessors were blinded to endoscopic BE images and histology. ROIs were first scored as nondysplastic or neoplastic. Level of confidence was assigned to the predicted diagnosis. Outcome measures were: (i) diagnostic performance of VLE assessors for identification of BE neoplasia in all VLE ROIs, defined as accuracy, sensitivity, and specificity; (ii) diagnostic performance of VLE assessors for only high level of confidence predictions; and (iii) interobserver agreement. Accuracy, sensitivity, and specificity for BE neoplasia identification were 79% (confidence interval [CI], 75–83), 75% (CI, 71–79), and 81% (CI, 76–86), respectively. When neoplasia was identified with a high level of confidence, accuracy, sensitivity, and specificity were 88%, 83%, and 90%, respectively. The overall strength of interobserver agreement was fair ( k = 0.29). VLE assessors can identify BE neoplasia with reasonable diagnostic accuracy in histopathology-correlated VLE ROIs, and accuracy is enhanced when BE neoplasia is identified with high level of confidence. Future work should focus on renewed VLE image reviewing criteria and real-time automatic assessment of VLE scans.